Student’s Perception on Implementation of Telephone Game as Icebreaker in English Learning at MTs Muslimat NU Palangka Raya - Tirtayasa Tirtayasa; Lesly Martha Cecylia Meka; Muhammad Subhan Fikri; Sulamit Syeba; Windy Rolan Rinaldo (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2026)
Low levels of students' engagement in English class are one of the challenges for teachers in English learning. The objective in this study is Exploring students’ perception of the telephone game as an icebreaker activity for English language learning at MTs Muslimat NU Palangka Raya. A quantitative descriptive method was used with data collected through a Likert-scale questionnaire distributed to 32 seventh-grade students who had already played the game in the English classroom. The questionnaire focused on four areas of the game, such as enjoyment, speaking confidence, pronunciation learning, and classroom atmosphere, as well as three items related to the game limitations. Data were analyzed and given as percentages to classify student perception. Despite this limitation, the findings suggest that the Telephone Game is useful in English learning. As a result, the telephone game in English learning class as alternate teaching approach to increase student engagement and reduce boredom in the English classroom. Therefore, the telephone game is recommended for English teachers to use in English learning classes.